Autophagy is Involved in Neuroprotective Effect of Alpha7 Nicotinic Acetylcholine Receptor on Ischemic Stroke - Xu, Zhe-Qi; Zhang, Jing-Jing; Kong, Ni; Zhang, Guang-Yu; Ke, Ping; Han, Ting; Su, Ding-Feng; Liu, Chong (Frontiers in Pharmacology, 2021)
α7 nicotinic acetylcholine receptor (α7nAChR) belongs to the superfamily of cys loop cationic ligand gated channels, which consists of homogeneous α7 subunits. Although our lab found activation of α7nAChR could alleviate ischemic stroke, the mechanism is still unknown. Herein, we explored whether autophagy is involved in neuroprotective effect mediated by α7nAChR in ischemic stroke. Transient middle cerebral artery occlusion (tMCAO) and oxygen and glucose deprivation (OGD/R) exposure were applied to in vivo and in vitro models of ischemic stroke respectively. Neurological deficit score and infarct volume were used to evaluate outcomes of tMCAO in vivo study. Autophagy related proteins were detected by Western blot, and autophagy flux was detected by tandem fluorescent mRFP-GFP-LC3 lentivirus. At 24 h after tMCAO, α7nAChR knockout mice showed worse neurological function and larger infarct volume than that in wildtype mice. PNU282987, a α7nAChR agonist, protected against OGD/R-induced neuronal injury, enhanced autophagy and promoted autophagy flux. However, the beneficial effects of PNU282987 were eliminated by 3-methyladenine (3-MA), an autophagy inhibitor. Moreover, we found that PNU282987 treatment could activate AMPK-mTOR-p70S6K signaling pathway in in vitro study, while the effect was attenuated by compound C, an AMPK inhibitor. Our results demonstrated the beneficial effect on neuronal survival via activation of α7nAChR was associated with enhanced autophagy, and AMPK-mTOR-p70S6K signaling pathway was involved in α7nAChR activation mediated neuroprotection.